TI_GERICHTE 12.2014.64 vom 22. Dezember 2014 , Inosservanza di un termine nella procedura dei casi manifesti: conseguenze - TI Tribunale d'appello (2014)
Inosservanza di un termine nella procedura dei casi manifesti: conseguenze